O paradoxo e o mito em Tutaméia - Caixeta, Maryllu de Oliveira (2008)
This work is focused on the structures of the paradox and the myth in the general organization of Tutaméia. We have chosen the first preface to the discussion of a poetic economy, which the author gives his point of view about it, and which is related to this conception of the whole set of preambles and stories: paradoxical and mythical, at the same time. These two structures, paradox and myth, are similar in one point of view, which brings these two aspects closer to the mimesis: the sense of uncertainty or wrongness between word and fact. By structuring the uncertainty of meaning, suggested by above-sense, the alternative reading is guaranteed as obstacle to hermeneutic control. Thus, the fight for truth is going beyond the truth itself or definitive sense. The assertion of that wrongness is also, by a paradox, the affirmation of the absence of mistake: all the senses are valued as unique perspectives in whole space of differences. The nonsense, when comes in series or in a compilation of texts, gives us the paradox and the myth, are archaic mechanisms, prior than the wisdom or instrumental reasoning. These mechanisms, no sense and myth, produce the surprises or the effects of discredit of the game: a kind of materialistic transcendence. The theme of the error and truth is central throughout Tutaméia. We have chosen, for analysis, twelve stories in which the theme of the mistake as limit of signification is more evident, in a way which these short tales become backgrounds for those above-senses, putting in central space the theme of the abysm between the word and the truth.